Tissue expansion as an aesthetic alternative for facial resurfacing: a single centre series of 92 patients - Agrawal, Neeraj K.; Choudhary, Aditya N.; Agrawal, Preeti (International Journal of Research in Medical Sciences, 2019)
Background: The visibility, vulnerability and social stigmata of facial scars whether by burn, nevi or trauma can be compelling for the patient as well as challenging for the surgeon. Restoration to normal form and aesthetics require tissue replacement which has good colour and texture match and produce minimal visible scarring. Although many other options are available for a given defect, tissue expansion offers the best alternative which meets almost all the criteria of an ideal procedure. Methods: Among 92 patients with deformities over various facial subunits were operated and expanders 50 ml to 300 ml inserted subcutaneously adjacent to the scar. Prior planning, accurate measurement and choice of ideal expander is extremely important. A precise and practical method of calculation for determination of amount and duration of expander was used. Any secondary deformity to adjoining vital structures was avoided. Results: Results were meticulously and critically analyzed. Different shapes, dimensions and volume of expanders were used depending on the anatomical site which was to be expanded. A total of 118 expanders were inserted in 92 patients. The average volume of tissue expanders used was 170.33 ml. Majority of the expanders used had volume of 200 ml (62.71%). Post-expansion volume was 240.67 ml and the over expansion done was 41.3% over the pre-expansion volume of 170.33 ml. Surgical outcome and cosmesis was assessed by the patient’s perspective and was considered fair by 57.61% patients. Conclusions: The study underlines the clinical application, reasons for overexpansion as well as shortcomings and complications of tissue expansion.